Design and Development of Web-Based E-CRM (Electronic Customer Relationship Management) at Bali Tangi - Zoltan, Daniel Syah Reza; Susila, Anak Agung Ngurah Hary; Githa, Dwi Putra (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi), 2024)
Bali Tangi is a company engaged in body care and beauty. Bali Tangi strives to enhance customer satisfaction in selling skincare and beauty products in the face of increasing business competition. The aim of this research is to design and develop a web-based E-CRM application to help the company strengthen customer relationships and improve customer satisfaction. The research method used consists of stages of problem and needs identification, literature study, analysis of CRM phases and business processes, system design and development according to needs, system testing, and system implementation through hosting. The results of functionality testing using black box testing indicate that the system can be used according to its functions. The final score of usability testing, measuring usability by users, is calculated from the total average of all indicators and shows a score of 4.13 with a satisfactory category for users.